2020
DOI: 10.1038/s41366-020-00716-y
|View full text |Cite
|
Sign up to set email alerts
|

Reduced lipolysis in lipoma phenocopies lipid accumulation in obesity

Abstract: Background Elucidation of lipid metabolism and accumulation mechanisms is of paramount importance to understanding obesity and unveiling therapeutic targets. In vitro cell models have been extensively used for these purposes, yet, they do not entirely reflect the in vivo setup. Conventional lipomas, characterized by the presence of mature adipocytes and increased adipogenesis, could overcome the drawbacks of cell cultures. Also, they have the unique advantage of easily accessible matched controls in the form o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…The application of our model to a series of datasets gathered from public sources, including GSE137631 ( 27 ), GSE141027 ( 28 ), GSE99374 ( 29 ), GSE151005 ( 30 ), Mangiola_2018 ( 26 ) and Atkins_2019 ( 31 ), revealed that a median of 10.6%, 3.3% and 10.4% of differentially abundant transcripts inferred by edgeR, the robust edgeR implementation (using estimateGLMRobustDisp) and DESeq2 respectively (using recommended analysis pipelines for data filtering, normalisation and modelling ( 32 , 33 )) had inflated statistics caused by the presence of outliers (Figure 4A ). The analyses were performed using tidybulk framework ( 34 ) and broom ( 35 ).…”
Section: Resultsmentioning
confidence: 99%
“…The application of our model to a series of datasets gathered from public sources, including GSE137631 ( 27 ), GSE141027 ( 28 ), GSE99374 ( 29 ), GSE151005 ( 30 ), Mangiola_2018 ( 26 ) and Atkins_2019 ( 31 ), revealed that a median of 10.6%, 3.3% and 10.4% of differentially abundant transcripts inferred by edgeR, the robust edgeR implementation (using estimateGLMRobustDisp) and DESeq2 respectively (using recommended analysis pipelines for data filtering, normalisation and modelling ( 32 , 33 )) had inflated statistics caused by the presence of outliers (Figure 4A ). The analyses were performed using tidybulk framework ( 34 ) and broom ( 35 ).…”
Section: Resultsmentioning
confidence: 99%
“…Hematoxylin and eosin-stained sections were visualized using ECLIPS 80i (Nikon Co., Tokyo, Japan). Adipocytes images in WAT were analyzed for adipocyte size using BZ-X800 analyzer software (Keyence Corp., Osaka, Japan) following the manufacturer's instructions [ 26 ]. The size of approximately 800–1000 adipocytes in WAT per mouse was assessed by measuring the diameter of the lipid droplets and averaged [ 27 ].…”
Section: Methodsmentioning
confidence: 99%
“…To identify molecular pathways that may be affected by the gene expression profiles we performed GO enrichment analysis followed by protein-protein-interaction (PPI) networks, as previously described 37,38 . Using the mouse data, we identified general GO categories like cellular components or developmental processes to be enriched with DEGs (Supplementary Table S2).…”
Section: Resultsmentioning
confidence: 99%